3(x+2)-2x=24

Simple and best practice solution for 3(x+2)-2x=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+2)-2x=24 equation:


Simplifying
3(x + 2) + -2x = 24

Reorder the terms:
3(2 + x) + -2x = 24
(2 * 3 + x * 3) + -2x = 24
(6 + 3x) + -2x = 24

Combine like terms: 3x + -2x = 1x
6 + 1x = 24

Solving
6 + 1x = 24

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 1x = 24 + -6

Combine like terms: 6 + -6 = 0
0 + 1x = 24 + -6
1x = 24 + -6

Combine like terms: 24 + -6 = 18
1x = 18

Divide each side by '1'.
x = 18

Simplifying
x = 18

See similar equations:

| 24x+2=26x-8 | | 4(5x-1)+2=-1 | | 2x+y=-16 | | (2x-3)=4 | | ln(x-8)+ln(x+9)=1 | | 5-x=3 | | 7-(3m)=1 | | 7-3m=1 | | 30k+88=163 | | 5(m+3)+2=2m+5 | | 1x-3y=2 | | 24=-(x+3) | | -2n+1-3n-n-4=7 | | 4(2X-1)+2=-1 | | 5(m+3)+2=m+5 | | y=x^2+4x-8 | | 2x-14+5x=20+1 | | 6k-2=26 | | 4x-8y=12 | | 6K-2=24 | | 3-6-2x=4 | | 5x-6x^2=0 | | 6(3x-1)=-42 | | 16x^2-4y^2+96x-40y+108=0 | | -9x^2-18=0 | | 39.96n+29.96=169.82 | | 5(m+3)2=2m+5 | | 20=-11-(13k-18k) | | -16t^2+48t+10=0 | | -3(4x)+9=9 | | 72-p^2=0 | | y+4-6y-5=90 |

Equations solver categories